Juridical Review of the Crime of Taking Women Run - Nurnashriady Jufri (Journal of Law Science, 2022)
This study aims to determine the application of material criminal law provisions for the crime of taking women away in the Unaaha District Court Decision Number 14/Pid.B/2011?PN.Unh and knowing the legal considerations in imposing criminal sanctions on the perpetrators of the crime of taking women away in the decision. Unaaha District Court Number 14/Pid.B/2011?PN.Unh, which was implementedat the Unaaha District Court. The data collection method used was the library method and the interview method, then the data obtained were analyzed qualitatively.